2018
DOI: 10.1007/s00417-017-3874-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bruch’s membrane opening and optic disc morphology to axial length and visual field defects in eyes with primary open-angle glaucoma

Abstract: The optic disc ovality was associated with both the axial length and MD, whereas BMO ovality was not. Attention should be paid to the influence of the axial length-related enlargement of the BMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…A similar observation was reported by Nakanishi and colleagues. 32 The BMO diameters increased in the present study with longer axial length in a nonlinear manner. There was only a slight enlargement of the BMO with longer axial length in eyes with an axial length of 26.0 mm and a relatively steep and linear increase in eyes with an axial length of >26.0 mm (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…A similar observation was reported by Nakanishi and colleagues. 32 The BMO diameters increased in the present study with longer axial length in a nonlinear manner. There was only a slight enlargement of the BMO with longer axial length in eyes with an axial length of 26.0 mm and a relatively steep and linear increase in eyes with an axial length of >26.0 mm (Figs.…”
Section: Discussionsupporting
confidence: 52%
“…Nakanishi et al . 15 also showed that BMO area was significantly associated with axial length. Our findings are consistent with those of previous reports, and indicate that BMO might undergo morphological changes during axial elongation.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, a negative correlation was observed between BMO-MRW and BMO area. The dependency of BMO-MRW on BMO size is well known 6,14,15 . With a larger BMO area, the axons of RGCs spread over an increased perimeter, and therefore, the measured BMO-MRW seems to be diminished while still possessing the same number of axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported previously that optic disc features that are assessed two-dimensionally based on the clinical disc margin of optic disc photographs and three-dimensionally based on the BMO from OCT scans often do not agree (36). Based on measurements of fundus photographs relative to the clinical disc margin, myopic optic disks have been reported to have a more oval configuration (11, 18, 30-32, 34, 37), a higher degree of disc tilt (12, 13,18,30,[33][34][35] and rotation (11,12,18,31,34,35). The current study confirms greater ovality (lower ovality index) in eyes in the high axial myopia group compared to eyes in the no and mild axial myopia groups using both semi-automated photograph-and automated OCT measurements.…”
Section: Discussionmentioning
confidence: 99%